Time variability of the gravitational constant and type Ia supernovae - Amendola, Luca; Corasaniti, Stefano; Occhionero, Franco (Arxiv, 1999)
We investigate to which extent a time variation of the gravitational constant or other fundamental constants affects the best fit of the Hubble diagram of type Ia supernovae. In particular, we show that a slow increase of $G$ in the past, below experimental constraints, can reconcile the SNe Ia observations with an open zero-$Λ$ universe.